Incidence of Pediatric Venous Thromboembolism After Elective Spine and Lower-Extremity Surgery in Children With Neuromuscular Complex Chronic Conditions: Do we Need Prophylaxis?. Issue 5 (May 2020) - Shore, Benjamin J.; Hall, Matt; Matheney, Travis H.; Snyder, Brian; Trenor, Cameron C.; Berry, Jay G.
Abstract : Background: The incidence of venous thromboembolism (VTE) after elective surgery in children with mobility impairments, including those with a neuromuscular complex chronic condition (NCCC), is unknown. Therefore, our objectives were to assess the incidence of VTE after elective spine and lower-extremity surgery in children with NCCC. Methods: A retrospective analysis of children with NCCC undergoing elective lower-extremity and/or spinal surgeries from 2005 to 2009 included in the Pediatric Health Information Systems Plus (PHIS+) database. VTE during hospitalization for surgery was assessed through abstraction and review of ultrasound (U/S) and computed tomography results by 2 independent reviewers. VTEs related to pre-existing central venous catheters were excluded. Results: There were 4, 583 children with NCCC who underwent orthopaedic surgery during the study period at 6 centers. Most were male (56.3%), non-Hispanic whites (72.7%), and had private insurance (52.2%). The most common NCCC diagnoses were cerebral palsy (46.7%), brain and spinal cord malformations (31.1%), and central nervous system degenerative conditions (14.5%). Forty children (0.9%) underwent U/S to assess VTE. Eighteen children (0.4%) underwent computed tomography to assess VTE. Four children (with cerebral palsy) had a positive U/S for a lower-extremity VTE (10-18 y of age), yet 2 had their VTE before surgery. Therefore, the adjusted VTE rate for children with NCCC undergoing orthopaedic lower-extremity or spine surgery was 4 per 10, 000 (2 cases per 4583 surgeries). Each of the 2 cases had a known coagulation disorder preoperatively. Only 10% of the cohort used compression devices, 3% enoxaparin, and 1.6% aspirin for prophylaxis. Conclusion: The rate of non–central-venous-catheter-related VTE associated with orthopaedic surgery in children with NCCC is very low and lower than rates reported in healthy children. Significance: To our knowledge, this is the first multi-institutional study reporting the incidence of VTE in children with NCCCs undergoing elective hip and spine surgery. These data support no additional prophylaxis is required in children with NCCC undergoing elective hip and spine surgery unless other known risk factors are also present.